Kilka uwag o tendencjach leksykalnych w nauczaniu języka polskiego jako obcego - Tambor, Jolanta (Postscriptum Polonistyczne, 2020)
The article presents the most important language rules and tendencies in teaching Polish as a foreign language. The author fully discusses word lists that are obligatory on different levels of proficiency in Polish language, pointing out to their advantages and disadvantages. She reminds about the necessity of completing such lists caused by intensive globalization and computerization. The article presents also problems concerning language used by young people nowadays, that is not only under the process of constant changes but it also becomes ‘out of date’ very quickly. Using fashionable words and words that have become commonly used as an example the author of the article proves the importance of language intuition while preparing lists of vocabulary for a certain level of language proficiency. The author concentrates also on describing problems concerning methods of teaching Polish as a foreign language that are connected with the rapid evolution of the language.